2019
DOI: 10.3168/jds.2018-15863
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Metagenomic evaluation of skin biopsies of udder sores in dairy cows

Abstract: The objectives of this study were (a) to evaluate skin biopsies of udder sores and negative control cows for the presence of mange and nonbacterial pathogens via histopathology and (b) to identify and compare bacterial abundance in the lesions of cows with udder sores and from the skin of healthy controls from the same farms. Cows from 3 dairy farms with (n = 23) and without (n = 12) udder sore lesions were enrolled, and punch biopsies (23 lesions, 23 negative control samples of cows with lesions, and 12 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
7
17
1
Order By: Relevance
“…Our results show an altered microbiota in both mild and severe UCD lesions compared to the control samples, manifested by decreased bacterial diversity and an increased proportion of certain bacterial genera and species. In line with our results on diversity, Sorge et al [17] found a lower bacterial diversity in samples from UCD lesions compared to control samples. A similar finding was also reported in a study on digital dermatitis, in which bacterial diversity decreased as the digital dermatitis lesions progressed in severity [32].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results show an altered microbiota in both mild and severe UCD lesions compared to the control samples, manifested by decreased bacterial diversity and an increased proportion of certain bacterial genera and species. In line with our results on diversity, Sorge et al [17] found a lower bacterial diversity in samples from UCD lesions compared to control samples. A similar finding was also reported in a study on digital dermatitis, in which bacterial diversity decreased as the digital dermatitis lesions progressed in severity [32].…”
Section: Discussionsupporting
confidence: 93%
“…have previously been identified in UCD lesions through culturing [3,13]. The genera Corynebacterium and Staphylococcus are also associated with bovine healthy skin from teat apices [38,39] and, in contrast to our results, Sorge et al [17] found a higher abundance of Corynebacterium spp. in controls than in UCD https://doi.org/10.1371/journal.pone.0242880.g008…”
Section: Plos Onecontrasting
confidence: 94%
See 3 more Smart Citations